2015
DOI: 10.1016/j.fct.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Iodine supplementation and drinking-water perchlorate mitigation

Abstract: Ensuring adequate iodine intake is important, particularly among women of reproductive age, because iodine is necessary for early life development. Biologically based dose-response modeling of the relationships among iodide status, perchlorate dose, and thyroid hormone production in pregnant women has indicated that iodide intake has a profound effect on the likelihood that exposure to goitrogens will produce hypothyroxinemia. We evaluated the possibility of increasing iodine intake to offset potential risks f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…For example, Manzon and Youson (1997) found that treatment with exogenous T 4 ameliorated perchlorate-induced decreases in the thyroid hormones of sea lamprey ( Petromyzon marinus ) larvae. Iodine supplementation to drinking water has been evaluated as a solution for preventing goitrogenic effects of perchlorate in humans (Lewandowski et al, 2015). However, an excess of iodide has been shown to induce toxic effects including inflammation, oxidative stress, and even autoimmune disease (Luo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Manzon and Youson (1997) found that treatment with exogenous T 4 ameliorated perchlorate-induced decreases in the thyroid hormones of sea lamprey ( Petromyzon marinus ) larvae. Iodine supplementation to drinking water has been evaluated as a solution for preventing goitrogenic effects of perchlorate in humans (Lewandowski et al, 2015). However, an excess of iodide has been shown to induce toxic effects including inflammation, oxidative stress, and even autoimmune disease (Luo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Iodate dose to offset perchlorate health effects. Physiologically based pharmacokinetic modeling relating perchlorate and iodine exposure to potential effects on thyroidal iodine uptake among sensitive populations, examined elsewhere (Lewandowski et al 2015), suggests that up to 1.5 µg I 2 /L (equivalent to 4 µg/L of dissolved iodate) would need to be added to drinking water to offset perchlorate concentrations up to 20 µg/L in drinking water, assuming consumption of approximately 3 L/d of treated water. In this study, a dosing ratio of total iodine (as atomic iodine) to perchlorate (as ClO 4 – ) of 1:2 (by mass) was used as a conservative assumption for iodine target concentrations in treated drinking water based on influent perchlorate concentrations.…”
Section: Proposed Approach To Iodine Additionmentioning
confidence: 99%
“…Because perchlorate inhibits thyroidal iodine uptake, additional iodine intake may be able to offset the potential thyroidal health impacts from perchlorate exposure (Lewandowski et al 2015, WHO 2013), and may, in fact, be “the most direct approach to reducing risk of perchlorate exposure to an individual” (Brent 2010). Direct iodine addition to drinking water could therefore represent a novel approach to offsetting the risk of low‐level perchlorate exposure in drinking water.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 Potassium iodate ingested within the human body is captured from the blood into the thyroid gland where it is first deoxidized into iodine to be incorporated in the biosynthesis of different thyroid hormones. 12,13 Adequate intake of iodine can be achieved by the consumption of iodized salt by the addition of potassium iodate to salt samples due to its good stability and bioavailability.…”
Section: Introductionmentioning
confidence: 99%